EDUCATIONAL PREREQUISITES FOR THE CERTIFICATE. - Leland, Thomas W. (The Accounting Review, 1945)
Looking at the question of desirable education from the standpoint of employers, accountants find many accounting practitioners who prefer employees with a liberal arts background. Some of these employers have stated that philosophy, history language, sociology, and physical science are useful to accountants in their work. Others have pointed out that emphasis on business and accounting courses in college frequently precludes an adequate program of cultural training. Accountancy needs men with varied talents and varied educational programs. It is also apparent that some accounting firms may require a few specialists in mathematics, statistics, English, economics, and possibly certain technical fields other than accounting. There are a considerable number of outstanding schools of business, and there is no question as to the advantage of college study of accounting and the related subjects of business law, economics, finance, and business. Especially is this true if the specialized study is preceded by a two-year study of liberal arts. Practitioners would do well to have a substantial proportion of their employees with this kind of technical training. The profession, by carefully selecting college-trained men, has a means of controlling standards, which is more effective than legislative requirements alone.